The Stochastic Gravitational Wave Background Generated by Cosmic String Networks. Issue Volume 10:Issue S306(2014) (1st July 2015) - Sousa, L.; Avelino, P. P.
Abstract: Cosmic string interactions often result in the formation of cosmic string loops that detach from the long string network and radiate their energy in the form of gravitational waves. Loop production occurs copiously throughout the cosmological evolution of a cosmic string network and the superimposition of their emissions gives rise to a stochastic gravitational In this essay, we briefly review our recent work on the stochastic gravitational wave background generated by cosmic string networks and introduce a set of numerical and analytical tools for the computation of this background.